Inhibition of the Hyaluronidase Enzyme Produced by Staphylococcus Bacteria Using Vasicine Alkaloids of the Vasica Plant - Fayyad, Sara Ali; Majeed, Majid Rasheed (Iraqi Journal of Science, 2024)
Hyaluronidase is an enzyme that breaks down primarily hyaluronic acid, thereby disrupting the structural integrity of the extracellular matrix (ECM) found in connective tissues, which is considered a virulence factor. The aim of this research was to study the effect of a plant-active compound (vasicine) that was separated from a plant sample as an inhibitor agent for the hyaluronidase enzyme that was isolated from Staphylococcus aureus, which is considered a virulence factor. 120 samples were randomly isolated from infected burns. The isolates showing highly hydrolyzed zones were identified. Cell growth as well as hyaluronidase activity are measured spectrophotometrically by the turbidity reduction assay. The results showed that 100 out of 120 clinical samples grew bacteria when cultured on blood agar medium. Also, it was found that of the 100 isolates, 56 (56%) belonged to S. aureus and had an inhibitory zone of hyaluronidase of 5–26 mm, and the inhibitory zone was increasing over time.